Characterization of the CDAA Diet-Induced Non-alcoholic Steatohepatitis Model: Sex-Specific Differences in Inflammation, Fibrosis, and Cholesterol Metabolism in Middle-Aged Mice - Kucsera, Dániel; Tóth, Viktória E.; Gergő, Dorottya; Vörös, Imre; Onódi, Zsófia; Görbe, Anikó; Ferdinandy, Péter; Varga, Zoltán V. (Frontiers in Physiology, 2021)
Background: The prevalence of non-alcoholic steatohepatitis (NASH) rapidly increases with associated metabolic disorders such as dyslipidemia, therefore, NASH is considered now an independent risk factor of cardiovascular diseases. NASH displays sex-linked epidemiological, phenotypical and molecular differences, however, little is known about the background of these sex-specific differences on the molecular level. Objectives: We aimed to assess sex-specific differences in the expression of inflammatory, and fibrotic genes, as well as in cholesterol metabolism, focusing on the expression of Pcsk9 in several tissues in a mouse model of NASH that shows the typical features of the human condition. Methods and Results: We fed 10 months old male and female C57Bl/6J mice with a NASH-inducing CDAA or corresponding control diet for 8 weeks. We have found that as compared the control male mice baseline hepatic Pcsk9 expression as well as serum PCSK9 level was significantly higher in females and both circulating PCSK9 level and the hepatic Pcsk9 gene were markedly decreased in female mice during NASH development. Histological analysis revealed that male and female mice develop similar degree of steatosis, however, fibrosis was more pronounced in males upon CDAA diet feeding. Strikingly, female mice have higher hepatic expression of the pro-inflammatory cytokines (Il1b, Ifng), and increased IL-1b cleavage by the NLRP3 inflammasome, and a decrease in Clec4f+ resident Kupffer cell population in comparison to males in the CDAA fed groups. Conclusions: This is the first demonstration that there are critical sex-specific differences during NASH development in middle-aged mice regarding inflammation, fibrosis and cholesterol metabolism and that changes in PCSK9 and IL-1b are likely important contributors to sex-specific changes during the transition to NASH